Relationships of Otolith Dimensions and Weight with Body Length of Three Lethrinid Species (Actinopterygii, Lethrinidae) from Yemen - L. A. Jawad; N. A. Al-Shwafi; G. Aguilar (Zoodiversity, 2025)
Relationships between fish length and otolith length, width, and weight were studied in three lethrinid species Lethrinus borbonicus Valenciennes 1830, Lethrinus lentjan (Lacepède 1802), and Lethrinus mahsena (Fabricius, 1775) collected from the south of the Red Sea at the costs of the Republic of Yemen. These relationships are important for future research into the biology of these species, including their diet, feeding habits, age, and growth. Linear regression models were used to investigate the relationships between otolith length and total fish length (TL), otolith weight and TL, and otolith width and TL. A non-linear regression model was used to investigate the relationship between otolith weight and TL. The morphometric relationships indicated that otolith length exhibited the highest correlation with total fish length among the other two otolith variables. This study is the first to examine the relationship between fish size and otolith size and weight in three lethrinid species obtained from the coast of the Red Sea in Yemen.